MODERNIZING MOUNTAIN EDUCATION: ESTABLISHING A TECHNOLOGY-BASED ISLAMIC BOARDING SCHOOL TO ENHANCE LEARNING QUALITY - Agung Wijaksono; Albadri Albadri (As-Sidanah, 2025)
Education is the cornerstone of national development; however, access to education in remote areas of Indonesia remains limited. Pondok Pesantren (Islamic Boarding Schools), as long-established Islamic educational institutions, hold significant potential in addressing this disparity, particularly in hard-to-reach mountainous regions. This article examines the role of Pondok Pesantren Al Fatih As Syafii in empowering education in remote areas through the integration of technology. By utilizing technology, Islamic boarding schools can enhance the quality of education, reduce disparities, and expand access to information for students. Beyond education, these institutions also function as centers for social and economic development, nurturing the character and skills of students. The appropriate application of technology can strengthen Pondok Pesantren's role in preparing a more competitive generation for the digital age. This research contributes to understanding how Pondok Pesantren can serve as key drivers in bridging the educational gap in remote areas and promoting a more inclusive, technology-enhanced learning environment.